Praktik Baik Supervisi Akademik Dalam Meningkatkan Kinerja Profesional Guru SMA Negeri 1 Kabanjahe - Eddyanto Bangun (UMSU, 2023)
The purpose of this study was to describe the implementation of academic supervision and good practices in the implementation of academic supervision at SMA 1 Kabanjahe, Karo Regency, North Sumatra Province. Academic supervision is a series of activities to help teachers develop the ability to manage the learning process in the classroom by the teacher. The results of this study indicate that in the implementation of effective supervision, good practices must be carried out by supervisors, namely they must be able to choose which one is most suitable to be implemented. The academic supervision techniques implemented are individual supervision techniques and group supervision techniques. Individual supervision practices carried out were: 1) class visits, 2) class observations, 3) individual meetings, 4) inter-class visits, and 5) self-assessment. Group techniques are carried out by involving a number of teachers in solving problems, talking and discussing with supervisors. The implementation of academic supervision at SMA Negeri 1 Kabanjahe includes (1) the planning stage with the activities of compiling a schedule for implementing supervision, evaluation programs, follow-up programs on the results of supervision evaluations, preparing administrative supporting documents, (2) implementation stages, (3) evaluation stages of supervision results, (4) follow-up stage.